The evolution of gender-related provisions in regional trade agreements - José-Antonio Monteiro (World Trade Organization (WTO), 2021)
Regional Trade agreements (RTAs) are sometimes considered as laboratories in which new types of provisions are negotiated to address recent trade-related issues. Although the inclusion of gender-related provisions in RTAs is not a recent phenomenon, only a limited but increasing number of RTAs refer explicitly to gender-related issues. These gender-related provisions are highly heterogeneous and differ in terms of location in the RTA, language, scope and commitments. Some of the most detailed gender-related provisions are found in stand-alone chapters on gender. Cooperation provisions on gender-related issues, including labour, health and social policy, remain the most common type of gender-related provisions found in RTAs. The remaining types of genderrelated provisions, included in a relatively limited number of RTAs, cover different issues, including upholding domestic gender-policies, implementing international gender-related agreements and instruments, and establishing institutional arrangements to oversee the implementation of the gender-related provisions and resolve issues through consultations. The first Global Trade and Gender Arrangement (GTGA), negotiated by Canada, Chile and New Zealand in 2020, builds on many of the gender-related provisions found in RTAs but sets out also new types of gender-related provisions, such as the principle not to weak or reduce the protection provided in gender equality laws and regulations to promote trade or investment.
Keywords: F13; F15; 330; Regional Trade Agreements; Gender; Women; Equality; Inclusiveness